Pregnancy with a Left Ventricular Assist Device: A Narrative Review - Matthew S. Abraham; Lijo M. Andrews; Harsha Deo; John Paul; Santhalakshmi Angappan; Abraham Samuel; Abey S. Abraham (Annals of Cardiac Anaesthesia)
This narrative review discusses the various challenges associated with the presence of a left ventricular assist device (LVAD) during pregnancy. Given the hemodynamic and coagulation changes associated with pregnancy, the presence of an LVAD adds a layer of complexity with respect to optimal management. This review will discuss the anesthetic considerations when dealing with this subset of patients who may have other comorbidities alongside their advanced heart failure. Additionally, this paper aims to review successful pregnancies with an LVAD placement focusing on the mode of delivery and hemodynamic management risk.